Relationship Between Knowledge And The Level Of Mothers' Compliance With Basic Infant Immunisation In The Working Area Of The Kuala Lempuing Health Centre, Bengkulu City In 2024 - Andriani, Zulfa; Susanti, Meri Epriana; Aprianti , Delta (Utami Publisher, 2026)
According to data from the Bengkulu City Health Department (2022), the health centres with the lowest rates of complete basic immunisation were Beringin Raya Health Centre (78%), Pasar Ikan Health Centre (73.3%), and Kuala Lempuing Health Centre (67%). At the Kuala Lempuing Community Health Centre in 2023, the number of infants who received complete immunisation reached 75.2%. There were 248 toddlers at the Kuala Lempuing Community Health Centre. The purpose of this study was to determine the relationship between knowledge and the level of compliance of mothers with basic infant immunisation in the Kuala Lempuing Community Health Centre working area, Bengkulu City, in 2024. The research method used was descriptive quantitative research with a cross-sectional approach. The sampling technique used was purposive sampling with a sample size of 38 people in the working area of the Kuala Lempuing Community Health Centre in Bengkulu City in 2024. The results of the univariate test analysis showed that almost all respondents (39.5%) had sufficient knowledge, while most respondents (57.9%) had a compliant level of adherence. The results of the bivariate analysis showed a relationship between knowledge (0.000) and the level of maternal adherence to basic infant immunisation in the Kuala Lempuing Community Health Centre Working Area in 2024. There is a relationship between knowledge and the level of compliance of mothers with basic infant immunisation in the working area of the Kuala Lempuing Community Health Centre, Bengkulu City, in 2024. The researchers suggest that the Kuala Lempuing Community Health Centre in Bengkulu City should further improve its immunisation services, monitor immunisation compliance, and provide health education on basic immunisation to increase mothers' motivation regarding the importance of basic immunisation for infants.